The good life : psychoanalytic reflections on love, ethics, creativity, and spirituality - Rubin, Jeffrey B. (State University of New York Press, 2004)
"In The Good Life Jeffrey B. Rubin demonstrates how psychoanalysis can make a profound contribution to the well-lived life by drawing on a neglected but potent aspect of psychoanalysis - its capacity to illuminate a psychology of health as well as illness. Rubin shows that, at its best, psychoanalysis can highlight both the ingredients of love, ethics, creativity, and spirituality, as well as the obstacles to experiencing them. Exploring the good life from this dual perspective provides an indispensable resource for helping us live with greater meaning and vitality."--Jacket